Evaluating the impact of severe sepsis 3‐hour bundle compliance on 28‐day in‐hospital mortality: A propensity adjusted, nested case–control study. Issue 8 (18th July 2022) - August, Benjamin A.; Griebe, Kristin M.; Stine, John J.; Hauser, Christian D.; Hunsaker, Todd; Jones, Mathew C.; Martz, Carolyn; Peters, Michael A.; To, Long; Belanger, Richard; Schlacht, Suzanne; Swiderek, Jennifer; et al.
Abstract: Objectives: The Centers for Medicare and Medicaid Services Severe Sepsis and Septic Shock Management Bundle (SEP‐1) assesses antibiotic administration, lactate measurement, and blood culture collection within 3 h of severe sepsis onset. The impact of the SEP‐1 3‐hour bundle among patients with severe sepsis is not extensively described. This investigation aimed to describe the impact of 3‐hour bundle compliance on 28‐day in‐hospital mortality in patients with severe sepsis. Study Design: This was a retrospective, propensity adjusted, nested case‐control study assessing the impact of compliance with a 3‐hour sepsis bundle among patients with severe sepsis. Setting: This study was conducted at a large, academic, tertiary care medical center in Detroit, Michigan from July 1, 2017 to December 31, 2019. Patients: Cases were defined as those suffering 28‐day in‐hospital mortality. Controls were defined as those surviving at or discharged by 28 days. Patients were separated based on 3‐hour bundle compliance or noncompliance. Nested and overall cohorts were assessed. Severe sepsis time zero was manually validated. Patients with shock, requiring vasopressors within 8 h of time zero, or those not meeting SEP‐1 inclusion criteria were excluded. Intervention: The primary outcome was the propensity adjusted odds of 28‐day in‐hospital mortality among 3‐hour bundle compliant versus noncompliant patients. Secondary outcomes included mortality for individual bundle element compliance, progression to septic shock, and predictors of mortality according to logistic regression. Results: A total of 325 compliant and 325 noncompliant patients were included. The median Sequential Organ Failure Assessment (SOFA) score was three in each group. There was no difference in propensity adjusted odds of mortality among those compliant versus noncompliant with the 3‐hour bundle (odds‐ratio [OR] 1.039; 95% CI: 0.721–1.497; p  = 0.838) or with individual bundle elements. SOFA score and female sex were predictors of mortality. Conclusions: Three‐hour bundle compliance did not impact 28‐day in‐hospital mortality in patients with severe sepsis. Further research is needed to understand the impact of 3‐hour bundle compliance on mortality in severe sepsis.